Angiotensin-converting enzyme gene I/D dimorphism does not play a major role in the susceptibility of Malaysian systemic lupus erythematosus patients - Lian, L.H.; Lau, T.P.; Ching, A.S.; Chua, K.H. (2012)
Systemic lupus erythematosus (SLE) is an autoimmune disease that causes systemic damage, involving auto-reactive antibodies and over-deposition of immune complexes. Susceptibility to SLE is believed to be multifactorial, and genetics is one of the proven etiological factors; it can affect SLE development, severity and prognosis. We investigated a possible association between the angiotensin-converting enzyme gene and susceptibility to SLE in the Malaysian population. PCR was employed for the determination of I/D dimorphism of this gene. The I allele was more frequent than the D allele in both the SLE patients (N = 170) and healthy controls (N = 190). However, there was no significant difference in the distribution of these two alleles between both groups studied (χ(2) = 0.284, P > 0.05). Interestingly, the DD homozygous genotype scored notably higher in the healthy control group (χ(2) = 7.568, P < 0.05), while the ID heterozygote was observed to be significantly associated with SLE (χ(2) = 11.143, P < 0.05). In conclusion, with respect to the Malaysian population, the DD genotype might play a protective role in the development of SLE while in contrast, those who carry the ID genotype might be at potential risk for onset of this disease.